2022
DOI: 10.1002/elan.202100396
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Nitrite Using an Asymmetrically Substituted Cobalt Phthalocyanine Conjugated to Metal Tungstate Nanoparticles

Abstract: This paper explores the synthesis and characterisation of an asymmetrical Co phthalocyanine (CoPc), and its covalent linking to two tungsten nanoparticles: bismuth tungsten oxide (Bi2WO6) and nickel tungsten oxide (NiWO4). The nanoparticles were also mixed with the CoPc. The CoPc, nanoparticles and their respective conjugates were used as electrocatalysts in the electrochemical detection of nitrite. The electrocatalysts studied in this work had sensitivities ranging from 3–133 μA/mM while the limits of detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Specically, the binuclear metal sites are 8 atoms apart from each other in bi-CoPc. The structures of both molecules were veried clearly by UV-vis 31 and FT-IR spectra 32,33 (Fig. S1a and b †).…”
Section: Electronic Structure Characterization Of Mono-copc and Bi-copcmentioning
confidence: 96%
“…Specically, the binuclear metal sites are 8 atoms apart from each other in bi-CoPc. The structures of both molecules were veried clearly by UV-vis 31 and FT-IR spectra 32,33 (Fig. S1a and b †).…”
Section: Electronic Structure Characterization Of Mono-copc and Bi-copcmentioning
confidence: 96%
“…The CoPc employed in this work is asymmetric. We have shown that asymmetry improves electrocatalytic activity of MPcs [12][13][14]. The asymmetrical CoPc is linked to detonation nanodiamonds (DNDs) covalently (CoPc@DNDs) or via π-π stacking (CoPc-DNDs(ππ)) for electrocatalytic oxidation of hydrazine as a test analyte.…”
Section: Introductionmentioning
confidence: 99%